Solid-state laser refrigeration of a composite semiconductor Yb:YLiF4 optomechanical resonator - Anupum Pant (Nature Portfolio, 2020)
Optically refrigerated resonators may be useful in optical devices and exploring quantum effects. Here, the authors show laser refrigeration of a semiconductor mechanical oscillator Yb:YLF host crystal and lowering the thermal load temperature.